Efficiency of Commercial Banks in Developing Countries: A Case Study of China Mainland, India and Indonesia - Lin, Jiayu (2014)
This study investigates the influence of the risk factor (equity) and environmental conditions have on the cost efficiency of three developing Asian countries, China mainland, India and Indonesia for cross-country comparisons of efficiency using a parametric approach, covering period of year 2006 to 2012. The goal of this analysis is to identify the impacts brought by equity and environmental variables on commercial banking efficiency in China mainland, India and Indonesia, especially the 2008 global financial crisis. To conduct this analysis, stochastic frontier analysis is utilized.